Cu2ZnSnSe4 Photovoltaic Absorber Layers Evaluated by Transmission X‐Ray Microscopy Tomography: Composition Fluctuations on the Length Scale of Grains. Issue 1 (30th December 2016) - Pruzan, Dennis S.; Caruso, Anna E.; Liu, Yijin; Lin, Yu; Beall, Carolyn; Repins, Ingrid; Toney, Michael F.; Scarpulla, Michael A.
Abstract : The origins of open‐circuit voltage deficits in Cu2 ZnSnS(e)4 ‐based solar cells have been an intense topic of research over the past few years as device efficiencies have never approached those of CuInGaSe2 based cells despite the materials sharing similar crystal and electronic structures. In this work, we use transmission X‐ray microscopy tomography to investigate the length scales over which elemental fluctuations occur. We find and show evidence of micron‐scale Cu to Zn anti‐correlations over a previously inaccessible combination of resolution and sample size that is consistent with the length scale of grains in this material. This result yields further insight into the causes of the large open‐circuit voltage deficits regularly seen in these devices as well as the challenges of achieving compositional homogeneity in this material. Abstract : Transmission X‐ray Microscopy Tomography is used to investigate compositional fluctuations in Cu2 ZnSnSe4 solar cells. The authors observe micron‐scale anticorrelation between Cu and Zn, a length scale consistent with fluctuations from grain to grain. This result yields further insight into the causes of V OC deficits and challenges with homogeneous growth in these materials.